Culturally-Embedded Educational Toys For Children Awareness: A Case Study on Julang Ngapak with User Centered Design - Anisa Silviana Putri; Nurul Fitriana Bahri; Hanif Azhar (Dinasti International Journal of Education Management And Social Science, 2024)
This research analyzes the application of the user-centered design (UCD) method in developing educational toys that focus on introducing culture, especially the Sundanese Julang Ngapak traditional house. The main goal of this research is to create products that are useful in entertainment and can also encourage children's cognitive, social, and emotional development. Qualitative methodology was applied through observation and interview techniques at SDN Cijagra 119 Bandung. The results showed that children were more enthusiastic about interactive and group games while tending to be more passive in formal learning activities. Aesthetic toy designs, characterized by the choice of relevant colors and shapes, have proven effective in attracting children's attention. Through an evaluation by media experts and child psychologists, the resulting product was declared safe, followed the curriculum, and was able to improve cognitive skills, such as cooperation and problem-solving. The best sketches integrate the Julang Ngapak structure with a puzzle system to support active learning. This research emphasizes the importance of the UCD approach in improving the quality and relevance of educational toys rooted in cultural values.